2020
DOI: 10.1242/jcs.242214
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule motor transport in the delivery of melanosomes to the actin-rich apical domain of the retinal pigment epithelium

Abstract: Melanosomes are motile, light-absorbing organelles that are present in pigment cells of the skin and eye. It has been proposed that melanosome localization, in both skin melanocytes and the retinal pigment epithelium (RPE), involves melanosome capture from microtubule motors by an unconventional myosin, which dynamically tethers the melanosomes to actin filaments. Recent studies with melanocytes have questioned this cooperative capture model. Here, we test the model in RPE cells by imaging melanosomes associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…A recent report suggests that inter-melanosome repulsion based on actin filament dynamics could maintain the spreading of melanosomes throughout the cytoplasm, without the need for microtubule-dependent transport [ 29 ]. Furthermore, another study showed that in retinal pigment epithelium (RPE) cells, microtubule transport is essential for fast long-range transport of melanosomes and that cytoplasmic dynein is indispensable for the passage of these organelles to an actin filament-dependent transport [ 30 ]. Therefore, the debate on this topic is still ongoing, as evidenced by the suggestion for a role of dynein components in melanosome maturation, position, and transfer to neighboring keratinocytes [ 31 ].…”
Section: Melanin Transfer Between Melanocytes and Keratinocytesmentioning
confidence: 99%
“…A recent report suggests that inter-melanosome repulsion based on actin filament dynamics could maintain the spreading of melanosomes throughout the cytoplasm, without the need for microtubule-dependent transport [ 29 ]. Furthermore, another study showed that in retinal pigment epithelium (RPE) cells, microtubule transport is essential for fast long-range transport of melanosomes and that cytoplasmic dynein is indispensable for the passage of these organelles to an actin filament-dependent transport [ 30 ]. Therefore, the debate on this topic is still ongoing, as evidenced by the suggestion for a role of dynein components in melanosome maturation, position, and transfer to neighboring keratinocytes [ 31 ].…”
Section: Melanin Transfer Between Melanocytes and Keratinocytesmentioning
confidence: 99%
“…Additionally, myosin-1 motors affect intracellular trafficking; function as tension-sensitive docks, phagocytosis, or tethers; and power membrane deformation [19][20][21][22]. Unconventional myosins are also proposed to be involved in the lightinduced translocation of mitochondria in photoreceptors and in human non-syndromic deafness [23][24][25][26][27][28]. Genetic mutations in myosins that lead to hearing loss have also been associated with retinal degeneration [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, melanin matures and accumulates in the apical compartment of the RPE cell. Despite this significant difference with KCs, Jiang et al (2020) have shown how RPE melanosomes move along MTs until they reach the apical, actin-rich, RPE cell domain, a process dependent on motor proteins [ 27 ]. Thereafter, melanin remains for a lifetime, unless aging or disease perturb it.…”
Section: Introductionmentioning
confidence: 99%